Method for preparing AlN particle reinforced magnesium-based composite material through stirring and high-speed shearing
The optimal high-speed shear mixing parameters were determined through the water simulation method, and AlN/GWZ magnesium-based composite materials were prepared by combining mechanical stirring and high-speed shear mixing technology, which solved the problems of uneven dispersion of AlN particles and low yield in the existing technology. , realizing the improvement of high-temperature mechanical properties of composite materials.
Patent Information
- Application Number
- CN202411470353.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-01-21
AI Technical Summary
The existing methods for preparing AlN particle-enhanced magnesium-based composites have problems such as low particle yield, uneven dispersion and serious air rolling, resulting in unsatisfactory particle enhancement effect and poor comprehensive mechanical properties.
Use the water simulation method to determine the optimal high -speed cutting and stirring parameters of the ALN particles dispersed, and prepare the Aln/GWZ magnesium -based composite material through mechanical stirring and high -speed cutting and stirring, including adding ALN particles at nearly semi -solid temperature at the magnesium alloy. Preliminary dispersion, then heating up at high speed shear and dispersing, and finally obtained composite materials through water cooling.
Effectively increased the income rate and uniform dispersing of the ALN particles, eliminated the problem of sedimentation and reunion of micron -level ALN particles, and realized the composite materials with uniform tissue and less defects. Rate.
Smart Images

Figure CN119332133A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite material preparation, and in particular relates to a method for preparing an AlN particle reinforced magnesium-based composite material through stirring and high-speed shearing. Background Art
[0002] Due to its low density, high specific strength and excellent casting performance, magnesium alloy has great application prospects in aerospace, electronic 3C and new energy fields. However, due to its poor wear resistance and high temperature performance, it cannot meet the use requirements of structural parts. By adding high-hardness and high-strength ceramic particles such as TiC, SiC and AlN to magnesium alloys, not only can the wear resistance of magnesium alloys be significantly improved, but also its high temperature performance can be improved. Among them, the preparation process of AlN particles is simple and low-cost. At the same time, the lattice parameters and crystal structure of AlN are similar to those of magnesium, which can effectively refine the grains of magnesium alloys and improve their mechanical properties. Therefore, the selection of AlN particles as reinforcements has been widely used in this industry.
[0003] At present, the most economical method for large-scale preparation of particle-reinforced magnesium-based composites is the stirring casting method. However, the preparation of AlN particle-reinforced magnesium-based composites by this method has problems such as low particle yield, uneven dispersion, and severe air entrainment, which leads to unsatisfactory particle reinforcement effect and poor comprehensive mechanical properties. At the same time, in order to obtain a composite material with uniform structure and excellent performance, the stirring process exploration cycle in its preparation process is long and easy to cause waste of experimental resources. Summary of the invention
[0004] The present invention aims to solve at least one of the technical problems in the related art to a certain extent. To this end, the main purpose of the present invention is to provide a method for preparing AlN particle reinforced magnesium-based composite materials by stirring and high-speed shearing, aiming to solve the problems of low particle yield, uneven dispersion and severe air entrainment in the existing preparation process.
[0005] The objective of the present invention is achieved through the following technical solutions:
[0006] A method for preparing an AlN particle reinforced magnesium-based composite material by stirring and high-speed shearing comprises the following steps:
[0007] 1) Determine the optimal high-speed shear stirring parameters for AlN particle dispersion using a water simulation method;
[0008] 2) melting the magnesium alloy under the protection of an inert gas to obtain a magnesium melt;
[0009] 3) cooling the magnesium melt obtained in step 2) to a temperature close to a semi-solid temperature, then adding AlN particles into the magnesium melt, and then mechanically stirring for preliminary dispersion to obtain a semi-solid melt;
[0010] 4) After the mechanical stirring is completed, the semi-solid melt is heated to the melting temperature and then subjected to high-speed shear dispersion to obtain a magnesium-based composite material melt.
[0011] 5) Water-cooling the magnesium-based composite material melt obtained in step 4) to obtain an AlN particle-reinforced magnesium-based composite material.
[0012] In certain specific embodiments, the water simulation method in step 1) is specifically: 10-20g of irregularly shaped PVC particles are placed in a transparent crucible filled with water, and then a high-speed shear stirrer is placed in the crucible; and the dispersion of the particles is observed and photographed at stirring speeds of 500, 1000, 1500, 2000 and 2500rpm / min, respectively, to obtain the optimal high-speed shear stirring parameters.
[0013] In some specific embodiments, the magnesium alloy in step 2) is Mg-10 Gd-3 Y-1Zn-0.4Zr (GWZ) alloy, the AlN particles are AlN particles coated with aluminum foil, and the addition amount of the AlN particles is 1wt.%-5wt.% of the magnesium alloy.
[0014] In some specific embodiments, the smelting in step 2) is specifically: smelting the magnesium alloy in a crucible of a resistance furnace at 720-750° C. under a CO 2 and SF 6 protective atmosphere until the magnesium alloy is completely melted.
[0015] In certain specific embodiments, the near semi-solid temperature in step 3) is 630° C., the process parameters of the mechanical stirring are 150-900 rpm / min, and the stirring time is 4-6 min.
[0016] In certain specific embodiments, the melting temperature in step 4) is 650-690° C., the high-speed shear stirring speed is 1000-3000 rpm / min, the stirrer is 30 mm away from the bottom of the crucible, and the stirring time is 1-3 min.
[0017] Furthermore, the stirring speed is 1500-2500 rpm / min.
[0018] Compared with the prior art, the present invention has at least the following advantages:
[0019] 1) The present invention adopts a water simulation method to effectively obtain the optimal high-speed shear stirring process parameters for dispersing AlN particles into magnesium-based materials, thereby avoiding a large number of exploratory casting experiments and reducing the waste of experimental resources;
[0020] 2) The present invention adopts a method combining mechanical stirring and high-speed shear stirring to prepare the AlN / GWZ magnesium-based composite material. The high-speed shear stirring under this process basically eliminates the sedimentation and agglomeration problems of micron-sized AlN particles, and effectively improves the yield and uniform dispersion of AlN particles;
[0021] 3) The AlN / GWZ magnesium-based composite material prepared by mechanical stirring and high-speed shear stirring method in the present invention has uniform structure and few defects, and does not require further deformation treatment to achieve improvement of comprehensive mechanical properties. The prepared AlN / GWZ magnesium-based composite material has 250°C high-temperature tensile strength, high-temperature yield strength and high-temperature elongation of 228.6 MPa, 175.2 MPa and 10.2%, respectively. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the specific embodiments of the present invention, the drawings required for use in the specific embodiments or the description of the prior art will be briefly introduced below.
[0023] Figure 1 This is a physical picture of the mechanical stirring blades for preparing magnesium-based composite materials by adding AlN composite powder in Examples 2-4 and Comparative Examples 1-2 provided by the present invention;
[0024] Figure 2 A physical picture of a high-speed shear mixer for preparing a magnesium-based composite material by adding AlN composite powder in Examples 2-4 provided by the present invention and a schematic diagram of its working principle;
[0025] Figure 3 This is a diagram showing the particle dispersion at different stirring speeds in the water simulation method in Example 1 provided by the present invention;
[0026] Figure 4 The metallographic structure diagram of the as-cast 1wt.% AlN / GWZ magnesium-based composite material prepared in Example 2 provided by the present invention;
[0027] Figure 5 The metallographic structure diagram of the as-cast 3wt.% AlN / GWZ magnesium-based composite material prepared in Example 3 provided by the present invention;
[0028] Figure 6 The metallographic structure diagram of the as-cast 5wt.% AlN / GWZ magnesium-based composite material prepared in Example 4 provided by the present invention;
[0029] Figure 7 The metallographic structure diagram of the as-cast 1wt.% AlN / GWZ magnesium-based composite material prepared in Comparative Example 1 provided by the present invention;
[0030] Figure 8The metallographic structure diagram of the as-cast 1wt.% AlN / GWZ magnesium-based composite material prepared in Comparative Example 2 provided by the present invention;
[0031] Fig. 9 This is the metallographic structure diagram of the cast matrix GWZ alloy provided by the present invention. DETAILED DESCRIPTION
[0032] The present invention will be further described in detail below in conjunction with the accompanying drawings and embodiments. The following embodiments are only illustrative and not restrictive, and the protection scope of the present invention cannot be limited thereto.
[0033] When a certain amount, concentration or other value or parameter is expressed in the form of a range, a preferred range, or a preferred upper and lower numerical limit, it should be understood that it is equivalent to specifically revealing any range by combining any pair of upper range limits or preferred numerical values with any lower range limit or preferred numerical value, regardless of whether the range is specifically disclosed. Unless otherwise indicated, the numerical range values listed herein include the endpoints of the range, and all integers and fractions within the range.
[0034] Unless otherwise indicated, all percentages, parts, ratios, etc. herein are by weight.
[0035] The materials, methods, and examples herein are illustrative and are not to be construed as limiting unless specifically stated.
[0036] In the following examples, the raw material Mg-10 Gd-3 Y-1Zn-0.4Zr (GWZ) alloy is a commercial alloy, specifically purchased from Chongqing Yuhua New Material Technology Co., Ltd.; the particle size of the reinforcement particle AlN is 5 to 10 μm;
[0037] In the following embodiments, the stirring device used for mechanical stirring is a handheld blade stirrer (manufacturer, model, parameters, etc.), the number of blades is 18, 9 blades on the upper and lower sides, the angle between the blades and the horizontal direction is 120°, and the stirring speed range is 0 to 950 rpm / min (such as Figure 1 As shown); the high-speed shear mixer is specifically composed of a stirring rotor and a perforated sleeve arranged on the outer circumference of the stirring rotor. The stirring rotor rotates at high speed to drive the melt to flow. The high-speed flowing melt will produce severe shearing effect when passing through the small holes on the sleeve wall, which is conducive to the uniform dispersion of particles in the melt. Among them, the stirring rotor has a diameter of 46mm, the number of blades is 4, the sleeve has a diameter of 45mm, the diameter of the holes on the sleeve is 3mm, the number is 216, and the stirring speed range is 0-3000rpm / min (as shown Figure 2 shown).
[0038] The test methods used in the following embodiments include:
[0039] The mechanical properties of the AlN particle reinforced magnesium-based composite material are reflected by testing the main properties of each test sample respectively; the main properties tested in this application include organizational morphology, mechanical properties, etc.
[0040] 1) Metallographic structure observation;
[0041] The OLYMPUS OLS4000 metallographic microscope was used to observe the structure of the test samples by sandpaper polishing combined with picric acid corrosion;
[0042] 2) Mechanical properties test
[0043] The samples were tested for high temperature mechanical properties at 250°C using a CMT5305 high temperature tensile testing machine in accordance with the GB / T 228.2-2015 method.
[0044] Example 1
[0045] This embodiment provides a water simulation method to determine the optimal high-speed shear stirring parameters for AlN particle dispersion, specifically:
[0046] 1) 15 g of irregularly shaped PVC particles were placed in a transparent crucible filled with water, and then a high-speed shear stirrer was placed in the crucible;
[0047] 2) Observe and photograph the dispersion of particles at stirring speeds of 500, 1000, 1500, 2000, and 2500 rpm / min.
[0048] This example is used to analyze the dispersion of particles at different high-speed shear stirring speeds in Example 1. Figure 3 As shown in the figure, it can be seen that: as the shear stirring speed increases, the uniform dispersion of the particles in the melt gradually increases; when the stirring speed is too high, the particles are broken and the melt is turbid, and it is very easy to cause air entrainment, and the performance of the composite material prepared by this process cannot be improved. Therefore, the high-speed shear stirring process in the present invention uses a stirring speed of 2000rpm / min, a distance of 30mm from the bottom of the crucible, and a stirring time of 2min. Therefore, the process parameters of high-speed shear stirring in the following embodiments are all selected as a stirring speed of 2000rpm / min, a distance of 30mm from the bottom of the crucible, and a stirring time of 2min.
[0049] Example 2
[0050] This embodiment provides a method for preparing an AlN particle reinforced magnesium-based composite material by stirring and high-speed shearing, which comprises the following steps:
[0051] 1) placing a commercial Mg-10Gd-3Y-1Zn-0.4Zr (GWZ for short) alloy in a crucible of a resistance melting furnace under a CO2 and SF6 protective atmosphere and melting it at 730°C until the alloy is completely melted to obtain an alloy melt;
[0052] 2) The alloy melt is cooled to 630°C, and then 1wt.% AlN particles coated with aluminum foil are added to the melt, followed by mechanical stirring (the stirring blades of the mechanical stirring are as follows Figure 1 As shown), the stirring speed is 600 rpm / min, and the stirring time is 5 min to obtain a semi-solid melt;
[0053] 3) After the mechanical stirring is completed, the semi-solid melt obtained in step 2) is heated to 680° C., the mechanical stirrer is taken out, and a high-speed shear stirrer is placed in the AlN / GWZ composite melt for high-speed shear stirring, the stirring speed is 2000 rpm / min, the distance between the stirrer and the bottom of the crucible is 30 mm, and the stirring time is 2 min to obtain a magnesium-based composite material;
[0054] 4) After the high-speed shearing is completed, the ingot of the AlN particle reinforced magnesium-based composite material (AlN / GWZ magnesium-based composite material) is obtained by water cooling at 690°C.
[0055] Example 3
[0056] This embodiment provides a method for preparing an AlN particle reinforced magnesium-based composite material by stirring and high-speed shearing, wherein the components and proportions are substantially the same as those in Example 2, except that the amount of AlN particles coated with aluminum foil is 3 wt.% of the magnesium-based alloy; and the preparation steps and parameters are the same as those in Example 2.
[0057] Example 4
[0058] This embodiment provides a method for preparing an AlN particle reinforced magnesium-based composite material by stirring and high-speed shearing, wherein the components and proportions are substantially the same as those in Example 2, except that the amount of AlN particles coated with aluminum foil is 5 wt.% of the magnesium-based alloy; and the preparation steps and parameters are the same as those in Example 2.
[0059] Comparative Example 1
[0060] This comparative example provides a method for preparing an AlN particle reinforced magnesium-based composite material by stirring and high-speed shearing, wherein the components and proportions are the same as those in Example 2; the preparation steps and parameters are basically the same as those in Example 2, except that the high-speed shear stirring process in step 3) is not performed, specifically:
[0061] 1) placing a commercial Mg-10Gd-3Y-1Zn-0.4Zr (GWZ for short) alloy in a crucible of a resistance melting furnace under a CO2 and SF6 protective atmosphere and melting it at 730°C until the alloy is completely melted to obtain an alloy melt;
[0062] 2) cooling the alloy melt to 630° C., then adding 1 wt.% AlN particles coated with aluminum foil into the melt, and then mechanically stirring at a speed of 600 rpm / min for 5 min to obtain a semi-solid melt;
[0063] 3) heating the semi-solid melt obtained in step 2) to 680° C. and continuing stirring at a stirring speed of 950 rpm / min for 2 min to obtain a magnesium-based composite material;
[0064] 4) After the mechanical stirring is completed, the ingot of the AlN particle reinforced magnesium-based composite material (AlN / GWZ magnesium-based composite material) is obtained by water cooling at 690°C.
[0065] Comparative Example 2
[0066] This comparative example provides a method for preparing an AlN particle reinforced magnesium-based composite material by stirring and high-speed shearing, wherein the components and proportions are the same as those in Example 2; the preparation steps and parameters are basically the same as those in Example 2, except that ultrasonic dispersion is used instead of the high-speed shear stirring process, specifically:
[0067] 1) placing a commercial Mg-10Gd-3Y-1Zn-0.4Zr (GWZ for short) alloy in a crucible of a resistance melting furnace under a CO2 and SF6 protective atmosphere and melting it at 730°C until the alloy is completely melted to obtain an alloy melt;
[0068] 2) cooling the alloy melt to 630° C., then adding 1 wt.% AlN particles coated with aluminum foil into the melt, and then mechanically stirring at a speed of 600 rpm / min for 5 min to obtain a semi-solid melt;
[0069] 3) After the mechanical stirring is completed, the semi-solid melt obtained in step 2) is heated to 680° C. and subjected to ultrasonic treatment for 5 minutes to obtain a magnesium-based composite material;
[0070] 4) After the mechanical stirring is completed, the ingot of the AlN particle reinforced magnesium-based composite material (AlN / GWZ magnesium-based composite material) is obtained by water cooling at 690°C.
[0071] Test example:
[0072] 1) Morphology test
[0073] The present application conducted a microstructure analysis of the magnesium-based composite materials prepared in Examples 2-7 using a metallographic microscope. The results are as follows: Figure 4 , 5 , 6, 7, 8 and 9, it can be seen from the figure that only mechanical stirring (Comparative Example 1) can achieve a certain degree of dispersion of AlN particles in the alloy matrix, but the uniform dispersion is still low, and there is a large AlN particle agglomeration area ( Figure 6 ), which is very unfavorable for composite strengthening. In contrast, on the basis of mechanical stirring, combined with high-speed shear stirring technology, the uniform dispersion of AlN particles can be achieved, and even if the AlN particle content increases, the dispersion of the particles is still very uniform, thereby improving the high-temperature comprehensive mechanical properties of the GWZ alloy; ultrasonic treatment (Comparative Example 2) can also improve the uniform dispersion of particles in the matrix, such as Figure 8 As shown, however, the agglomeration of AlN particles still exists. Compared with ultrasonic treatment, high-speed shear stirring has a more significant effect on the uniform dispersion of particles; Figure 8 is the metallographic structure of the base alloy obtained in specific embodiment 2, compared with Figure 4 , Figure 5 , Figure 6 The metallographic structures of the cast 1wt.% AlN / GWZ, 3wt.% AlN / GWZ, and 5wt.% AlN / GWZ composite materials show that the GWZ alloy grains are significantly refined after the addition of AlN particles. In summary, it can be seen that by dispersing AlN particles in magnesium-based alloys using the stirring + high-speed shear stirring method, not only can the dispersion uniformity of AlN particles in magnesium-based alloys be greatly improved, but also the filling rate of AlN particles in magnesium-based alloys can be effectively improved, and the grains of magnesium-based alloys can be refined, thereby greatly improving the high-temperature comprehensive mechanical properties of magnesium-based alloys.
[0074] 2) Mechanical properties test
[0075] The present application also tests the comprehensive mechanical properties of the AlN particle reinforced magnesium-based composite materials prepared in Examples 2-4 at 250°C, and the results are shown in Table 1:
[0076] Table 1 Comprehensive mechanical properties of AlN particle reinforced magnesium-based composite materials at 250°C in Example X and Comparative Example X
[0077]
[0078] It can be seen from the table that the method of mechanical stirring combined with high-speed shear stirring in the present invention can effectively improve the high-temperature mechanical properties of the matrix GWZ magnesium alloy. Among them, the comprehensive mechanical properties of the cast 3wt.% AlN / GWZ composite material at 250°C reach the best, and its tensile strength, yield strength and elongation are 228.6MPa, 175.2MPa and 10.2% respectively.
[0079] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. These modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention, and they should all be included in the scope of the claims and specification of the present invention.
Claims
1. A method for preparing an AlN particle reinforced magnesium-based composite material by stirring and high-speed shearing, characterized in that: The steps include: 1) Determine the optimal high-speed shear stirring parameters for AlN particle dispersion using a water simulation method; 2) melting the magnesium alloy under the protection of an inert gas to obtain a magnesium melt; 3) cooling the magnesium melt obtained in step 2) to a temperature close to a semi-solid temperature, then adding AlN particles into the magnesium melt, and then mechanically stirring for preliminary dispersion to obtain a semi-solid melt; 4) After the mechanical stirring is completed, the semi-solid melt is heated to the melting temperature and then subjected to high-speed shear dispersion to obtain a magnesium-based composite material melt. 5) Water-cooling the magnesium-based composite material melt obtained in step 4) to obtain an AlN particle-reinforced magnesium-based composite material.
2. The method for preparing AlN particle reinforced magnesium-based composite material by stirring and high-speed shearing according to claim 1, characterized in that: The water simulation method described in step 1) is specifically as follows: 10-20 g of irregularly shaped PVC particles are placed in a transparent crucible filled with water, and then a high-speed shear stirrer is placed in the crucible; and the dispersion of the particles is observed and photographed at stirring speeds of 500, 1000, 1500, 2000 and 2500 rpm / min, respectively, to obtain the optimal high-speed shear stirring parameters.
3. The method for preparing AlN particle reinforced magnesium-based composite material by stirring and high-speed shearing according to claim 1, characterized in that: In step 2), the magnesium-based alloy is Mg-10 Gd-3 Y-1Zn-0.4Zr alloy, the AlN particles are AlN particles coated with aluminum foil, and the addition amount of the AlN particles is 1wt.%-5wt.% of the magnesium-based alloy.
4. The method for preparing AlN particle reinforced magnesium-based composite material by stirring and high-speed shearing according to claim 1, characterized in that: The smelting in step 2) is specifically as follows: the magnesium-based alloy is smelted in a crucible of a resistance melting furnace at 720-750° C. under a protective atmosphere of CO 2 and SF 6 until the magnesium alloy is completely melted.
5. The method for preparing AlN particle reinforced magnesium-based composite material by stirring and high-speed shearing according to claim 4, characterized in that: In step 3), the near semi-solid temperature is 630° C., the process parameters of the mechanical stirring are 150-900 rpm / min, and the stirring time is 4-6 min.
6. The method for preparing AlN particle reinforced magnesium-based composite material by stirring and high-speed shearing according to claim 1, characterized in that: Step 4) The melting temperature is 650-690° C., the high-speed shear stirring speed is 1000-3000 rpm / min, the stirrer is 30 mm away from the bottom of the crucible, and the stirring time is 1-3 min.
7. The method for preparing AlN particle reinforced magnesium-based composite material by stirring and high-speed shearing according to claim 1, characterized in that: The stirring speed is 1500-2500 rpm / min.
Citation Information
Patent Citations
AlN / Al particle reinforced magnesium aluminum rare earth based composite material and preparation method thereof
CN114277277A
Magnesium-based composite material with improved heat resistance and preparation method thereof
CN114277297A
Aluminum-based composite material refining device and preparation method
CN115572853A
Method for improving agglomeration of micron-sized AlN particles in magnesium-rare earth-based composite material
CN117230341A